INSTILLING THE VALUES OF RELIGIOUS MODERATION THROUGH LOCAL CULTURE IN ELEMENTARY SCHOOL STUDENTS - Faridah, Siti; Rahman, Sidqi Aulia; Putri, Mutammimah; Nulinnaja, Ratna (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
The issue of interfaith intolerance in Indonesia is increasingly exacerbated by the spread of misinformation and extremist doctrines through digital technology. This threatens social harmony and fosters anti-religious moderation attitudes. Amid these challenges, it is essential to environments, to create a generation that is tolerant and respectful of religious differences. This study aims to describe how the values of religious moderation are instilled through local culture at elementary school in SDN 1 Balun Lamongan, which is know for its religious diversity. The research employs a descriptive qualitative approach using observation, interviews, and documentation methods. The findings indicate that SDN 1 Balun Lamongan implements various religious and extracurricular activities involving all students, regardless of their religious backgrounds. Activities such as interfaith celebrations and artistic collaborations, involving students from Islam, Christianity, and Hinduism, are conducted. This implementation has successfully shaped students into tolerant individuals who respect each other and can cooperate despite religious differences. The application of religious moderation values through local culture at SDN 1 Balun Lamongan has had a positive impact on fostering harmony and interfaith unity among the students from an early age.